Moreau's decomposition theorem

From Wikimization

(Difference between revisions)
Jump to: navigation, search
m (Proof)
(Proof)
Line 14: Line 14:
<ul>
<ul>
-
<li>1<math>\Rightarrow</math>2: For all <math>p\in K</math> we have <math>\langle z-x,p-x\rangle=\langle y,p-x\rangle=\langle y,p\rangle\leq0</math>. Then, by the characterization of the projection it follows that <math>x=P_{\mathcal K}z</math>. </li>
+
<li>1<math>\Rightarrow</math>2: For all <math>p\in K</math> we have <math>\langle z-x,p-x\rangle=\langle y,p-x\rangle=\langle y,p\rangle\leq0</math>. Then, by the characterization of the projection it follows that <math>x=P_{\mathcal K}z</math>. Similarly, for all <math>q\in K^\circ</math>\langle z-y,q-y\rangle=\langle x,q-y\rangle=\langle x,q\rangle\leq0</math> and thus <math>y=P_{\mathcal K^\circ}z</math>.</li>
<li>1<math>\Rightarrow</math>2</li>
<li>1<math>\Rightarrow</math>2</li>
</ul>
</ul>

Revision as of 15:36, 10 July 2009

Moreau's theorem is a fundamental result characterizing projections onto closed convex cones in Hilbert spaces.

Let LaTeX: \mathcal K be a closed convex cone in the Hilbert space LaTeX: (\mathcal H,\langle\cdot,\cdot\rangle) and LaTeX: \mathcal K^\circ its polar. For an arbitrary closed convex set LaTeX: \mathcal C in LaTeX: \mathcal H, denote by LaTeX: P_{\mathcal C} the projection onto LaTeX: \mathcal C. For LaTeX: x,y,z\in\mathcal H the following two statements are equivalent:

  1. LaTeX: z=x+y, LaTeX: x\in\mathcal K, y\in\mathcal K^\circ and LaTeX: \langle x,y\rangle=0
  2. LaTeX: x=P_{\mathcal K}z and LaTeX: y=P_{\mathcal K^\circ}z

Proof

Let LaTeX: \mathcal C be an arbitrary closed convex set in LaTeX: \mathcal H, LaTeX: u\in\mathcal H and LaTeX: v\in\mathcal C. Then, it is well known that LaTeX: v=P_{\mathcal C}u if and only if LaTeX: \langle u-v,w-v\rangle\leq0 for all LaTeX: w\in\mathcal C. We will call this result the characterization of the projection.

  • 1LaTeX: \Rightarrow2: For all LaTeX: p\in K we have LaTeX: \langle z-x,p-x\rangle=\langle y,p-x\rangle=\langle y,p\rangle\leq0. Then, by the characterization of the projection it follows that LaTeX: x=P_{\mathcal K}z. Similarly, for all LaTeX: q\in K^\circ\langle z-y,q-y\rangle=\langle x,q-y\rangle=\langle x,q\rangle\leq0</math> and thus LaTeX: y=P_{\mathcal K^\circ}z.
  • 1LaTeX: \Rightarrow2
Personal tools